It is the responsibility of intellectuals to speak the truth and to expose lies - Chomsky, Noam. (New York New Press, 2017)
As a nineteen-year-old undergraduate in 1947, Noam Chomsky was deeply affected by articles about the responsibility of intellectuals written by Dwight Macdonald, an editor of Partisan Review and then of Politics. Twenty years later, as the Vietnam War was escalating, Chomsky turned to the question himself, noting that ?intellectuals are in a position to expose the lies of governments? and to analyze their ?often hidden intentions.?
Keywords: Intellectualism